Strategy-Proof Allocation of Objects Revisited - Tommy Andersson; Lars-Gunnar Svensson (Lund University, School of Economics and Management, Department of Economics, 2018)
We consider an allocation problem with a finite number of objects, and agents that demand at most one of the objects. The study provides a characterization of a class of strategy-proof price mechanisms. A mechanism belongs to the class if and only if the price space is restricted in a special way and, given that restriction, the outcome prices are minimal. The domain of the mechanisms is the set of general preference profiles (R_1,R_2,…,R_n), i.e., where R_a is agent a's rational, monotonic and continuous preference ordering over objects and prices.
Keywords: D44; D47; D63; D78; D82; 330; Characterization; House-allocation; Strategy-proofness; Multiobject auction